Gingival blood flow changes following periodontal access flap surgery using laser Doppler flowmetry - M. Retzepi (Blackwell Synergy, 2007)
Aim: To investigate the pattern of gingival blood flow changes following periodontal access flap surgery by laser Doppler flowmetry (LDF). Material and methods: Fourteen patients with chronic periodontitis presenting upper anterior sites with pocket depth X5mm after initial treatment were included in the study. Periodontal access flap surgery was performed on the experimental areas and LDF recordings were taken at baseline, following anaesthesia, immediately postoperatively and on days 1, 2, 3, 4, 7, 15, 30 and 60 of healing, at nine predetermined sites per flap. Results: Significant ischaemia was observed at all flap sites following anaesthesia and immediately postoperatively. At the alveolar mucosal sites, a peak increase of the gingival blood flow was observed on postoperative day 1 (po0.001), which persisted until day 7 (p50.012) and resolved by day 15. The mucosal sites close to the flap periphery presented higher blood perfusion compared with the sites located centrally in the flap. The microcirculatory perfusion of the buccal and palatal papillae was maximum on postoperative day 7 (p50.013 and o0.001, respectively) and returned to baseline by day 15. Conclusion: Topographically distinct areas of the periodontal access flap consistently present different patterns of microvascular blood flow alterations during the woundhealing period.